General and Disease-Specific Use of Outcomes Scores for the Shoulder: A Survey of Aossm, Aana, and Isakos Members. Issue 3 (September 2014) - Provencher, Matthew T.; Frank, Rachel M.; Scuderi, Matthew G.; Solomon, Daniel J.; Ghodadra, Neil S.; Bach, Bernard R.; McCarty, Eric; Romeo, Anthony A.
Abstract: Objective: To report on the knowledge and use of both general and disease-specific shoulder outcomes scores among orthopedic surgeons.Methods: A 22-question Internet survey was administered to members of the American Orthopaedic Society for Sports Medicine, the Arthroscopy Association of North American, and the International Society of Arthroscopy, Knee Surgery, and Orthopedic Sports Medicine via voluntary e-mail participation. Questions targeted demographic information, preferred surgical management of shoulder conditions, and the preferred use of shoulder outcomes instruments in clinical practice.Results: Excluding defunct and duplicate e-mails among membership societies, a total of 3892 unique e-mails were sent, from which 1129 surveys were returned and were fully completed (29%). The largest number of respondents were in private practice (52%); 21% were in academia; and 26% were in a mix of settings. As for location, 74% practiced in the United States, 10% in Europe, 8% in Mexico/South America, and 6% in Asia. A total of 31% total respondents used scores all or most of the time, and 30% used scores at least some of the time. Respondents felt that the 3 most commonly utilized shoulder scores were the American Shoulder and Elbow Surgeons (ASES) score, the University of California at Los Angeles (UCLA) score, and the Constant score. The majority of respondents (76%) performed all-arthroscopic instability repairs. The ASES and Western Ontario Shoulder Instability Index (WOSI) scores were the most preferred measures to monitor instability patients, whether or not the scores were actually implemented in their practice. Most perform between 10 and 25 superior labrum anterior-posterior repairs per year and preferred the ASES, UCLA, and Constant scores for these repairs; rotator cuff repair preferred outcomes instruments were similar. When asked to choose 1 score for all shoulder conditions, the ASES was the clear favorite.Conclusions: This study reports the knowledge and utilization of shoulder scores for both general and disease-specific conditions. Most respondents preferred the ASES score for most shoulder conditions; however, other scores, such as the WOSI, the Constant, and the Short-Form (SF)-36/12, were popular. This information offers insight into the current and future use of shoulder outcomes both for general and disease-specific use.